Case Report: Genetic Creutzfeldt–Jakob Disease With a G114V Mutation and One Octapeptide Repeat Deletion as a Mimic of Frontotemporal Dementia - Lin, Xue; Xu, Yichen; Zhen, Zhen; Xiao, Kang; Chen, Xu; Yang, Jigang; Guan, Hongzhi; Shi, Qi; Dong, Xiaoping; Wang, Jiawei; Guo, Yanjun (Frontiers in Neurology, 2022)
Genetic Creutzfeldt–Jakob disease (gCJD) characterized by mutations in the prion protein (PrP) gene (PRNP) contributes to approximately 10–15% of the overall human prion diseases. Here, we report a rare mutation in the PRNP gene in a Han-Chinese family. A 36-year-old man initiated with anxiety and depression followed by progressive dementia, cogwheel-like rigidity combined with tremors, and he was diagnosed with frontotemporal lobar dementia in the first 2 years. The disease progression was relatively slow, and the patient developed into akinetic mutism in 4 years. To characterize the disease, following the pedigree studies, neuropsychological examination, neuroimaging studies, real-time quaking-induced conversion (RT-QuIC) examination, and so on were conducted. We eventually identified a rare mutation of G114V combined with one octapeptide repeats deletion (1-ORPD) in the PrP in the patient by DNA sequencing. In addition, the same mutation and deletion were subsequently identified in the patient's mother without any syndromes. His maternal grandmother had a late onset of the disease in her 60s. Given that 1-OPRD has never been reported in human prion disease before, our first report that both G114V mutation and 1-OPRD appear in the family would forward our understanding of the etiological mechanisms of the gCJD.